Assessing Environmental Literacy for Flood Disaster Mitigation in Elementary School - Iin Novianti; Nurasyah Dewi Napitupulu; Novalina; Mau'izah; Fadil; Irfandi Lahamado (Universitas Negeri Malang, 2025)
Abstract: This research aims to assess the environmental literacy of students at SDN Rogo, Dolo Selatan, Central Sulawesi, and its relationship with their flood disaster mitigation skills. A quantitative descriptive approach was used, with total sampling of all upper-grade students. Data were collected through a questionnaire evaluating students' understanding and attitudes toward flood disasters. Environmental literacy was measured using four indicators: ecological knowledge, cognitive skills, environmental affect, and pro-environmental behavior. These indicators reflect students' understanding of ecological concepts, analytical abilities regarding environmental issues, emotional awareness, and participation in sustainability practices. The findings show that students scored 78.85 percent in ecological knowledge, 76.34 percent in cognitive skills, 77.30 percent in environmental affect, and 78.13 percent in pro-environmental behavior, resulting in an overall environmental literacy score of 77.08 percent, categorized as good. These results indicate that students have a strong foundation in environmental understanding and are actively engaged in sustainable practices. Their cognitive and behavioral skills contribute to disaster risk reduction through informed decision-making and preventive actions. However, the study is limited to a single school context and relies on self-reported data, which may introduce response bias. Future research should involve broader samples and observational methods to improve the validity of the findings. Abstrak: Penelitian ini bertujuan untuk menilai literasi lingkungan siswa di SDN Rogo, Dolo Selatan, Sulawesi Tengah, dan kaitannya dengan kemampuan mitigasi bencana banjir mereka. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan sampling total mencakup semua siswa kelas tinggi. Data dikumpulkan melalui kuesioner yang mengevaluasi pemahaman dan sikap siswa terhadap bencana banjir. Literasi lingkungan diukur menggunakan empat indikator: pengetahuan ekologi, keterampilan kognitif, afeksi lingkungan, dan perilaku pro-lingkungan. Indikator-indikator ini mencerminkan pemahaman siswa terhadap konsep ekologi, kemampuan analitis terkait isu lingkungan, kesadaran emosional, dan partisipasi dalam praktik keberlanjutan. Hasil penelitian menunjukkan bahwa siswa memperoleh skor 78,85 persen dalam pengetahuan ekologi, 76,34 persen dalam keterampilan kognitif, 77,30 persen dalam afeksi terhadap lingkungan, dan 78,13 persen dalam perilaku pro-lingkungan, dengan skor literasi lingkungan keseluruhan sebesar 77,08 persen, yang dikategorikan sebagai baik. Hasil ini menunjukkan bahwa siswa memiliki dasar yang kuat dalam pemahaman lingkungan dan aktif terlibat dalam praktik berkelanjutan. Keterampilan kognitif dan perilaku mereka berkontribusi pada pengurangan risiko bencana melalui pengambilan keputusan yang terinformasi dan tindakan pencegahan. Namun, studi ini terbatas pada konteks satu sekolah dan bergantung pada data yang dilaporkan sendiri, yang dapat menimbulkan bias respon. Penelitian selanjutnya sebaiknya dapat melibatkan sampel yang lebih luas dan metode observasional untuk meningkatkan validitas temuan.